Prediction for hydrolysis of ethylene oxide via fuzzy logic and PID control - Norhanifah Abdul Halim,; Norliza Abd. Rahman,; Jarinah Mohd Ali, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Monoethylene glycol (MEG) or Ethylene Oxide is an important chemical in plastic and automotive industry as mixed ingredients or cooling liquid. It is produced from ethylene oxide via hydrolysis at 200ºC and 22 atm. The ratio of the ethylene oxide with water should be maintain at 1:20 to reduce the formation of diethylene glycol and higher homologs. Objective of this study is to predict a production of MEG using fuzzy logic. Others parameters such as level, temperature, composition and pressure are consider constant in this research as this study focusing on single input, single (SISO) output strategy. For fuzzy logic prediction, the type of model chosen is Mamdani with triangular membership function, input 1, input 2, and output which refer to error, feedback, and production of ethylene glycol respectively. 11 rules has been construct in this research. The rules may contain “AND” or “OR” conjunctions. The “error” represents the difference between the value feedback and the output. The results for fuzzy rules give highest product of MEG (6.91) at error of 0.102 and 0.8 of feedback. The gain of proportional, integral, and derivative are 0.2, 0.2, and 0.1 respectively.